Internet- and mobile-based trauma-focused intervention for adolescents and young adults with posttraumatic stress disorder: a study protocol of a proof-of-concept feasibility study - Schulte, Christina; Zarski, Anna-Carlotta; Sachser, Cedric; Rosner, Rita; Ebert, David Daniel (European Journal of Psychotraumatology, 2022)
Introduction: Although evidence-based treatments for posttraumatic stress disorder (PTSD) in adolescents and young adults exist, affected youth do not have sufficient access to these treatments due to structural and attitudinal barriers. Internet- and mobile-based interventions (IMIs) can help fill this healthcare gap, but such programmes have not yet been sufficiently evaluated in youth with PTSD. Aim: This study aims to investigate the feasibility of an IMI for youth with PTSD in a one-arm, non-randomised, prospective proof-of-concept feasibility study. Methods: We aim to recruit 32 youth between 15 and 21 years old with clinically relevant posttraumatic stress symptoms (CATS ≥ 21), who will receive access to the IMI. The IMI consists of nine sessions involving psychoeducation, emotion regulation and coping skills, written-based imaginal exposure, cognitive restructuring and relapse prevention. Participants will be guided by an eCoach, who provides weekly semi-standardised written feedback on completed sessions and adherence reminders. We will use a formal feasibility framework to assess different dimensions of feasibility: (1) recruitment capability and resulting sample characteristics, (2) data collection procedures and outcome measures, (3) acceptability of the IMI and study procedures, (4) resources and ability to manage and implement the study and IMI and (5) participants’ responses to the IMI in terms of symptom severity and satisfaction. Additionally, potential negative effects related to the intervention will be assessed. Assessments take place pre-, mid- and post-intervention and at follow-up, including semi-structured clinical telephone interviews for PTSD diagnostics at pre- and post-intervention assessment. Qualitative interviews will be conducted to investigate the youth perspectives on the IMI. Discussion: This study aims to determine the feasibility of a guided IMI for youth with PTSD to adapt the IMI as closely as possible to youth needs and to inform the design, procedure and safety management of a large-scale efficacy RCT. Trial registration:German Clinical Trials Register identifier: DRKS00023341. HIGHLIGHTS: Evidence-based care for adolescents after trauma is not widely available.• This study evaluates the feasibility of a guided trauma-focused Internet intervention as a time- and location-independent low-threshold treatment option for adolescents and young adults with posttraumatic stress disorder.
CRIS-Team Scopus Importer:2022-08-12
Keywords: adolescents and young adults; imaginal exposure; internet- and mobile-based intervention; posttraumatic stress disorder; Trauma; trauma-focused cognitive behaviour therapy; written-based exposure